Gender neutral proper names: current situation and perspectives - Jana Valdrová (Gender a Výzkum, 2023)
Personal proper names are part of a community's language inventory. To a large extent, they verbalise gender stereotypes, expectations and norms, power relations,  political circumstances, and how minorities are treated. In my paper I analyse the current socio-onomastic representation of gender-neutral names in the context of naming practices in the Czech Republic. More specifically, I examine what factors might explain the decreased use of these names, which, paradoxically, differ from other names in that they have an extended functionality. From a linguistic and legal perspective I inquire into how Czech naming practices stigmatise the sexual otherness of non-binary people and trans people in Czech society. In the conclusion I set out the conditions that must be met for gender-neutral names to be freely available to the entire population.